Successful marketing reaearch : the complete to getting and using essential information about your customers and competitors - Hester, Edward L. (New York : John Wiley, 1996)
Business
Keywords: Marketing research; Market research; Business; Advertising; Media; Trade; Marketing plan; Communication; Customer; Marketing information systems